Motor Imagery in Unipolar Major Depression - Bennabi, Djamila; Monnin, Julie; Haffen, Emmanuel; Carvalho, Nicolas; Vandel, Pierre; Pozzo, Thierry; Papaxanthis, Charalambos (Frontiers in Behavioral Neuroscience, 2014)
Background: Motor imagery is a potential tool to investigate action representation, as it can provide insights into the processes of action planning and preparation. Recent studies suggest that depressed patients present specific impairment in mental rotation. The present study was designed to investigate the influence of unipolar depression on motor imagery ability. Methods: Fourteen right-handed patients meeting DSM-IV criteria for unipolar depression were compared to fourteen matched healthy controls. Imagery ability was accessed by the timing correspondence between executed and imagined movements during a pointing task, involving strong spatiotemporal constraints (speed/accuracy trade off paradigm). Results: Compared to controls, depressed patients showed marked motor slowing on both actual and imagined movements. Furthermore, we observed greater temporal discrepancies between actual and mental movements in depressed patients than in healthy controls. Lastly, depressed patients modulated, to some extent, mental movement durations according to the difficulty of the task, but this modulation was not as strong as that of healthy subjects. Conclusion: These results suggest that unipolar depression significantly affects the higher stages of action planning and point out a selective decline of motor prediction.